Pojok literasi untuk meningkatkan minat baca: Studi pada TK PKK Desa Sawahan Kec. Turen Kab. Malang - Aprilia, Andini; Hakiem, Ahmad Haidar; Nadlir, Firkhanun; Fauzia, Yusma Lana; Febriani, Roiyan One (Maliki Interdisciplinary Journal, 2024)
Literacy activities are activities that important in the world of education, and indeed The main activity of this literacy is reading literacy. The community service team makes it happen establishment of a reading corner in the Berangas area, Barito Kuala. The Berangas area is the location was chosen for the establishment of a reading corner because at This area has many pre-aged children school or appropriate school age target audience for this service activity. Community service activities are carried out in 3 stages, namely the planning stage, which is an activity to find out conditions and situation of the target audience. Second stage namely the implementation and report preparation stages activities, this stage is the founding process reading corner at a predetermined location, namely on Jalan Berangas, Barito Kuala Regency, at a time prepare equipment for establishment of the reading corner. This equipment in the form of reading material consisting of story books children, children's encyclopedia, to books can broaden children's insight. Last stage namely preparing reports on service activities society which contains a description of implementation of activities aimed at target audience. With activities The establishment of this reading corner will be able to improve interest in reading in children both pre-school and children of school age, as well as capable provides simple reading facilities that can used by the target audience to increase knowledge and interest in reading from an early age.